Modelling Route Cost and Performance Evaluation of Public Buses in Kathmandu: A Case Study of Sajha Yatayat Electric Buses - Karn, Rupesh; KC, Mohan Dhoj; Devkotab, Bishnu Prasad (Journal on Transportation System and Engineering, 2026)
This study assesses the operational and financial performance of Sajha Yatayat’s electric buses in Kathmandu, highlighting route cost estimation, revenue generation and service productivity. A mixed method approach was applied including field surveys, key informant interviews (KIIs), operational data analysis and statistical evaluation through SPSS. Signal to Noise (SNR) analysis was used to identify and rank the key factors affecting route cost which emphasizes vehicle and battery depreciation, route distance, energy price fluctuation, labor costs and fare structures. A cost allocation model was developed based on vehicle hours (VH), vehicle kilometers (VK) and peak vehicles (PV) to estimate route wise operational expenses for fiscal year 2023/24. The model projects a total operational cost of NRs. 139.4 million with higher costs related with longer routes requiring peak vehicles. The performance evaluation such as revenue/cost ratio, operating cost per vehicle kilometer, operating cost per passenger and revenue per vehicle kilometer show overall profitability and financial sustainability with revenue/cost ratio between 1.2 to 1.3. Annual revenue reached NRs. 50.97 million supported by 3.45 million passengers, showing increasing ridership and growing public acceptance.